Relationship-based practice and digital technology in child and family social work: Learning from practice during the COVID-19 pandemic. (March 2022) - Copson, Ruth; Murphy, Anne M; Cook, Laura; Neil, Elsbeth; Sorensen, Pernille
Vital services provided by social workers to children in care or on the edge of care were largely delivered "online" during the COVID-19 pandemic. This paper explores the potential impact of these changes on vulnerable children and their families. Relationship-based practice is integral to social work and the shift to digital communication during the COVID-19 pandemic has led to accelerated practice changes and implications for relationship building both with and between service users. Going forward, social workers and other professionals are likely to move to an increasingly hybrid model of communication, combining both digital and face-to-face methods. This article identifies the impact of digital communication on relationships in professional practice, drawing on three studies of digital communication in the UK carried out at the University of East Anglia. The first considered how child protection social workers responded to the challenges of COVID-19, the second looked at how children in care were keeping in touch with their birth families and the third focused on the approaches being taken to moving children from foster care to adoptive families. Five themes related to relationships were identified across all three studies: the significance of the age and developmental stage of the child; the frequency of contact and communication; digital literacy/exclusion; the impact of the lack of sensory experience; and the importance of the relationship history. The article concludes with implications for utilising digital methods in building and maintaining relationships in practice and highlights the need to consider both the inner and outer worlds of those involved.